Implementation of Competitive Adaptation and Resilience Strategies Post Covid-19 Pandemic in Halal Food SMEs - Haque, Marissa Grace (Airlangga Journal of Innovation Management, 2024)
SME industry saves the nation's economy, 10.79 million people (7.71 percent) of the Indonesian population work in providing accommodation and food. Knowing the survival ability of industry players on a mike scale is very important. This study used a mixed method, with descriptive analysis to determine the survival ability of the "Pempek Bicik Nina", Palembang, company post-pandemic. Using the SWOT analysis, and internal-external weighting, the Four Step Strategy determines the most appropriate strategy, to be able to overcome challenges by taking advantage of all possible opportunities. Results showed that several weaknesses must be immediately corrected to optimize revenue potential, in the form of more extensive digital marketing, and innovation in product variants, including embracing more public figures as catalysts to leverage. Innovation in product variants is also needed to maintain the attractiveness so that it can continue to attract old customers, as well as attract the interest of new consumers. The cost leadership strategy was maintained. The ability to control costs, and operational efficiency, is very important to maintain profitability and competitiveness. By adapting to all digital world business developments and its product innovation, "PBN", can maintain business continuity. In particular, by combining digital marketing strategies, product innovation, embracing more public figures, and cost leadership strategies, halal SMEs "PBN" can continue to develop and succeed in the halal SME culinary market.